Different clinical presentations of a rare venous malformation-inferior vena cava agenesis - Machado,Marta (2021)
Abstract Introduction: Inferior vena cava agenesis is one of the most uncommon anomalies of this vessel, with an estimated prevalence of 0.0005-1% in the general population. However, around 5% of the patients younger than 30 years with a diagnosis of deep vein thrombosis have this anomaly. Methods and material: Report of two clinical cases of inferior vena cava agenesis with different clinical presentations. Clinical case 1: A 40-year-old man was admitted with a 3 days history of unilateral lower limb swelling and pain, gradually progressing to the inability to walk. On physical examination he had swelling, bruising and tenderness involving leg and thigh and prominent engorged superficial abdominal collateral veins. Venous Doppler Ultrasound showed left deep venous thrombosis extending from popliteal vein to common iliac vein. A computed tomography angiogram showed agenesis of the infrarenal vena cava and patent renal veins draining in to the azygous system and hemiazygous systems. The patient as discharged with rivaroxaban and compression stockings. At 2 months follow up he was asymptomatic and still anticoagulated. Clinical case 2: A 35 year- old woman, with a previous history of recurrent lower limb varicose veins surgery and left internal malleolar ulcer at 30 years presented at medical department 3 years later with complains of ulcer recurrence. A computed tomography angiogram revealed an absent infrahepatic vena cava, prominently dilated azygos and hemiazygos veins with enlarged retroperitoneal collaterals. The patient initiated dressing care with oxide zinc and oral rivaroxaban. Discussion/conclusion: The majority of cases remain asymptomatic. However, when symptomatic, the majority present as proximal DVT involving the iliac and femoral veins. CT or MRI should be the imagiological methods used to diagnose this anomaly. No clear consensus has been reached on therapeutic strategy, other than long-term anticoagulation and elastic stockings.